Proceedings of a Workshop on Livelihood Strategies of the Rural Poor and the Environment (Technical report series (HIVOS (Organization). South India Regional Office) ;, 1998)
Held at the Indian Institute of Management, Bangalore, 9-12 December 1995; with reference to India.